Nutritional management of a dog with hepatic enzymopathy suspected to be secondary to copper-associated hepatitis: a case report - Poblanno Silva, Francisco Manuel; Grant, Caitlin Elizabeth; Ribeiro, Érico de Mello; Verbrugghe, Adronie (Frontiers in Veterinary Science, 2023)
A 4-year-old, female-spayed American Bulldog presented to the Ontario Veterinary College’s Health Sciences Centre’s Clinical Nutrition Service for nutritional management of hepatic enzymopathy and suspected copper-associated hepatitis. Medical history revealed a 3-month history of gradually increasing serum ALT. Additional diagnostics included negative Leptospira titters, normal bile acids, and laparoscopic liver biopsy. Histopathology findings were consistent with diffuse moderate vacuole hepatocellular degeneration; mild positive copper staining; mild chronic lymphoplasmacytic hepatitis both portal and central; mild biliary hyperplasia. Hepatic copper quantification results were above normal ranges (630 ug/g dry-tissue), but below those seen in familial copper-associated hepatitis (>800-1000 ug/g dry-tissue). The patient was prescribed ursodeoxycholic acid, recommended to be fed a homemade diet (HMD) and referred for a nutrition consult. Two days before the nutrition consult, serum ALT was within normal range. The body condition score was 5/9, with a good muscle condition score and the dog’s appetite and body weight remained stable. Energy intake was appropriate for maintenance. Key nutrient levels of all diets reported were compared to industry standards (AAFCO, NRC, and FEDIAF). Diet history included a commercially available raw meat-based diet (RMBD), of unknown copper content; a high energy commercial dry food (HEC), with copper content higher than the maximum recommended by FEDIAF and immediately before nutrition consult the patient had been eating an unbalanced HMD (HMD1) for 4 weeks. HMD1 was low in copper and deficient in the hepatoprotectant nutrients vitamin E and zinc. As per owner's preference and to accommodate the patient’s unique nutritional needs a HMD addressing key nutrients for liver disease was formulated (HMD2), with copper content just above the recommended minimum. The new diet was found palatable and the patient’s body weight, body and muscle condition scores remained unchanged. Two months after starting HMD2, all bloodwork values remained within the normal range, including ALT. The reduction of dietary copper content likely reduced serum ALT. However, unbalanced diets cause a risk of nutrient deficiencies and excess. This dog was maintained with no known adverse effects on a complete and balanced HMD diet with a moderately low copper content, moderate protein, and inclusion of hepatoprotective nutrients